Early exposure of pregnant women to non‐steroidal anti‐inflammatory drugs delivered outside hospitals and preterm birth risk: nationwide cohort study. (22nd March 2021) - Quantin, C; Yamdjieu Ngadeu, C; Cottenet, J; Escolano, S; Bechraoui‐Quantin, S; Rozenberg, P; Tubert‐Bitter, P; Gouyon, J‐B
Abstract : Objective: To assess the risk of preterm birth associated with nonsteroidal anti‐inflammatory drugs (NSAIDs), focusing on early exposure in the period from conception to 22 weeks of gestation (WG). Design: National population‐based retrospective cohort study. Setting: The French National Health Insurance Database that includes hospital discharge data and health claims data. Population: Singleton pregnancies (2012–2014) with a live birth occurring after 22WG from women between 15 and 45 years old and insured the year before the first day of gestation and during pregnancy were included. We excluded pregnancies for which anti‐inflammatory medications were dispensed after 22WG. Methods: The association between exposure and risk of preterm birth was evaluated with GEE models, adjusting on a large number of covariables, socio‐demographic variables, maternal comorbidities, prescription drugs and pregnancy complications. Main outcome measures: Prematurity, defined as a birth that occurred before 37WG. Results: Among our 1 598 330 singleton pregnancies, early exposure to non‐selective NSAIDs was associated with a significantly increased risk of preterm birth, regardless of the severity of prematurity: adjusted odds ratio (aOR) = 1.76 (95% CI 1.54–2.00) for extreme prematurity (95% CI 22–27WG), 1.28 (95% CI 1.17–1.40) for moderate prematurity (28–31WG) and 1.08 (95% CI 1.05–1.11) for late prematurity (32–36WG), with non‐overlapping confidence intervals. We identified five NSAIDs for which the risk of premature birth was significantly increased: ketoprofen, flurbiprofen, nabumetone, etodolac and indomethacin: for the latter, aOR = 1.92 (95% CI 1.37–2.70) with aOR = 9.33 (95% CI 3.75–23.22) for extreme prematurity. Conclusion: Overall, non‐selective NSAID use (delivered outside hospitals) during the first 22WG was found to be associated with an increased risk of prematurity. However, the association differs among NSAIDs. Tweetable abstract: French study for which early exposure to non‐selective NSAIDs was associated with increased risk of prematurity. Tweetable abstract: French study for which early exposure to non‐selective NSAIDs was associated with increased risk of prematurity.